2012
DOI: 10.1186/1752-153x-6-44
|View full text |Cite
|
Sign up to set email alerts
|

Production and validation of model iron-tannate dyed textiles for use as historic textile substitutes in stabilisation treatment studies

Abstract: BackgroundFor millennia, iron-tannate dyes have been used to colour ceremonial and domestic objects shades of black, grey, or brown. Surviving iron-tannate dyed objects are part of our cultural heritage but their existence is threatened by the dye itself which can accelerate oxidation and acid hydrolysis of the substrate. This causes many iron-tannate dyed textiles to discolour and decrease in tensile strength and flexibility at a faster rate than equivalent undyed textiles. The current lack of suitable stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Ellagic acid, which is likely formed from hydrolysable tannin [56], was detected at 15.6 minutes from those black samples ( Figure 8B). In one of the black thread samples of Persian velvet (acc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellagic acid, which is likely formed from hydrolysable tannin [56], was detected at 15.6 minutes from those black samples ( Figure 8B). In one of the black thread samples of Persian velvet (acc.…”
Section: Resultsmentioning
confidence: 99%
“…Those black pile samples appeared to be more brittle than other colored samples and those black piles missing from the velvets. This was likely caused by iron-mordant being used with tannins to achieve the black color [56,57] page 95-96.…”
Section: Resultsmentioning
confidence: 99%
“…15 Furthermore, a highly cross-linked network of ferric tannate was found to exhibit a rough and porous surface, 16 …”
Section: 6mentioning
confidence: 99%
“…Hydrolysable tannins are glucose esters of phenolic acids (gallic acid, ellagic acid) and when combined with iron ions form blueblack iron (III) tannate dye complexes (Wilson 2012). Condensed tannins (proanthocyanidins) are polymers of flavan-3-ol (catechin) monomers, and when com-bined with iron ions form green-black coloured dye complexes (Wilson 2012;Wilson, Carr, and Hacke 2012). Daniels (1999a) suggested that condensed tannins (i.e.…”
Section: The Production Of Iron Tannate-dyed Māori Textilesmentioning
confidence: 99%